Investigation of Impervious surface and Urban Surface Temperature in Qaemshahr - Taher Safarrad; Yadollah Yousefi; Atefeh Rezaei taleei (تحقیقات کاربردی علوم جغرافیایی)
Information on a variation of impervious surface is useful for understanding urbanization and its impacts on the hydrological cycle, water management, surface energy balances, urban heat island, and biodiversity. This research attempts to detect impervious surfaces and its changes by satellite imagery in Qaemshahr. The relationship between impervious surfaces and changes in land surface temperature in the city was investigated. For this purpose, after obtaining three images in 1978, 2000, and 2017, and performing the necessary preprocessing, the reflection values of the infrared spectrum and ground surface temperature in the study area were calculated. The reflectance of this spectrum was investigated in various land uses vegetation, asphalt and building areas in two parts of the urban and the suburb.  Using the results of ANOVA and Tukey these properties compared to different land uses. By the difference between Permeable surfaces and impervious surfaces, the impervious surface index was calculated. The results of the detection and comparison of the three surveyed images showed that the impervious surfaces in Qaemshahr were significantly increased from 1978 to 2017. In the next step, by calculating the land surface temperature, it was determined that the temperature of the impervious surfaces is higher than the other parts of the study area. An increase in the population of the city followed by an increase in urban construction has led to an increase in impervious surfaces and a reduction in green space and this has caused a rise in city temperatures. The results of this study showed that increasing impervious surfaces has led to an increase of around 4 degrees in the city's temperature. Finally, any increase in the impervious surface at the city will lead to unsustainability in the urban environment, if not accompanied by proper planning.